Neighborhood Prison Admission Rates and the Sunbelt: Variation in Imprisonment, Concentrated Disadvantage, and Their Relationship Across the United States - Campbell, Walter (Crime & delinquency, 2020)
Regional differences in the use of prison are, in part, due to cultures of punishment within Sunbelt states. To date, this has been largely studied at the state level, ignoring the smaller geographic areas in which the effects of imprisonment are deeply felt. We employ a novel data set to examine the relationship between prison and region and regional variation in the relationship between concentrated disadvantage and neighborhood imprisonment. We find that region affects neighborhood prison admission rates in unexpected ways, and that the relationship between concentrated disadvantage and prison admissions varies in magnitude by region. We discuss the implications of these findings for better understanding the impact of region and the processes that lead to imprisonment.